The relationship between students’ perceptions and their engagement through self-regulated learning - Maridha Normawati; Frieda Maryam Mangunsong Siahaan; Rose Mini Agoes Salim; Shahnaz Safitri; Astri Setiamurti; Atikah Ainun Mufidah (Journal of Education and Learning (EduLearn), 2026)
The engagement of psychology students in statistics courses requires improvement because the learning material is challenging to understand. This leads to the emphasis on the teaching ability of lecturers, which is one of the external factors to increase student engagement. Internal factors such as self-regulated learning can impact engagement during lectures. Therefore, this study examines the role of self-regulated learning as a mediator in the relationship between students’ perceptions of creativity fostering teacher behavior (p-CFTB) and the engagement of psychology undergraduates in the statistics class. A mediation test using RStudio software was utilised to examine the role of self-regulated learning as a mediator, and 533 undergraduate psychology students from different parts of Indonesia participated in this study. The results showed that self-regulated learning partially mediated the relationship between p-CFTB and student engagement with the indirect effect value was greater than the direct effect. Therefore, student engagement is more affected by self-regulated learning in its role as a mediator than when it occurs without a mediator. Consequently, this study found that the role of various actors, such as lecturer behavior to foster creativity is needed to improve student self-regulated learning so that student engagement can function at its most effective.